Legal Analysis of the Policy on Appointing Foreign Nationals as Directors of State-Owned Enterprises - Raisha Tiara Hasnakusumah (Jurnal Daulat Hukum, 2026)
The amendment to Law Number 19 of 2003 on State-Owned Enterprises through Law Number 16 of 2025 has opened the possibility for foreign nationals to serve as directors of State-Owned Enterprise Limited Liability Companies (Persero BUMN). This policy has generated debate as it is considered a means of enhancing professionalism, corporate governance quality, and the competitiveness of SOEs. This study aims to examine the rationale behind the appointment of foreign nationals as directors of Persero BUMN and to assess its compatibility with the principle of state control as stipulated in Article 33 of the 1945 Constitution. Employing a normative juridical method with statutory and conceptual approaches, the study finds that the policy emerged as a response to structural challenges faced by SOEs, including limited competitiveness, corporate governance issues, and the need for professional leadership in an increasingly competitive global environment. Furthermore, the appointment of foreign directors is not inconsistent with the principle of state control, provided that the state retains effective authority over their recruitment, appointment, and supervision. To safeguard national interests, a specific vetting mechanism should be established, particularly for SOEs operating in strategic and sensitive sectors.